Empirical Evidence of the Deaton's Paradox in Europe - Ruschka, Adam; Janíčko, Martin, 1983-; Chytilová, Helena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2021)
The theory of consumption is a crucial part of economic science and it has gone through severe changes over the last century. The most pronounced theory is the Permanent Income Hypothesis by Milton Friedman. With the progress towards the positivity of economics, the incentive to test all theoretical frameworks on the date increased. Cambell and Deaton had tested for validity of the PIH in 1989 and found out, that the predictions of the theory do not match the data. The consumption patterns exhibits smaller changes, when confronted with unexpected change in income (excessive consumption smoothing), and bigger changes, when confronted with the expected changes in income (excessive sensitiveness) than the PIH predicts. This discrepancy between the theory and the data is now known as the Deaton’s paradox. The aim of this thesis is to test, whether is the excessive consumption smoothing present in Europe. In order to do so, a new model using the dynamic panel estimator is developed. The dataset contains the data from 26 European countries from 2000 to 2019. Newer researches of the Deaton’s paradox have come with the hypothesis, that the discrepancy is caused by the low granularity of the data used. In order to test this possibility, both quarterly and monthly data are used. Based on the results of the model we conclude, that the predictions of the PIH are not in line with the data and the granularity of the data used has no impact on this fact.
Vedoucí práce: Martin Janíčko
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: ekonomie [obor dipl. práce]; diplomové práce; master's theses